2015
DOI: 10.1371/journal.pone.0131587
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Independent ADME Properties and Tentative Identification of Metabolites of α-Mangostin from Garcinia mangostana in Mice by Automated Microsampling and UPLC-MS/MS Methods

Abstract: The information about a marker compound's pharmacokinetics in herbal products including the characteristics of absorption, distribution, metabolism, excretion (ADME) is closely related to the efficacy/toxicity. Also dose range and administration route are critical factors to determine the ADME profiles. Since the supply of a sufficient amount of a marker compound in in vivo study is still difficult, pharmacokinetic investigations which overcome the limit of blood collection in mice are desirable. Thus, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Subsequently, α-MG was detected to be transported into various cell lines (macrophage-like THP-1, hepatic HepG2, enterocyte-like Caco-2, and colon HT-29), where it underwent phase II metabolism and biotransformation to get converted into other xanthones [126]. By in vitro metabolism studies using tissue homogenates, α-MG was proven to be metabolized mainly via the liver and small intestine [127,128]. With regards to the formation of metabolites, the glucuronidated, bis-glucuronidated, dehydrogenated, hydrogenated, oxidized, and methylated α-MG were tentatively identified [128].…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, α-MG was detected to be transported into various cell lines (macrophage-like THP-1, hepatic HepG2, enterocyte-like Caco-2, and colon HT-29), where it underwent phase II metabolism and biotransformation to get converted into other xanthones [126]. By in vitro metabolism studies using tissue homogenates, α-MG was proven to be metabolized mainly via the liver and small intestine [127,128]. With regards to the formation of metabolites, the glucuronidated, bis-glucuronidated, dehydrogenated, hydrogenated, oxidized, and methylated α-MG were tentatively identified [128].…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
“…By in vitro metabolism studies using tissue homogenates, α-MG was proven to be metabolized mainly via the liver and small intestine [127,128]. With regards to the formation of metabolites, the glucuronidated, bis-glucuronidated, dehydrogenated, hydrogenated, oxidized, and methylated α-MG were tentatively identified [128]. In vivo animal studies showed that the majority of α-MG occurred in the plasma as phase II metabolites and only minimal amounts as free forms after oral administration [129].…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
See 3 more Smart Citations